A critical approach to security in the Middle East: towards sustainable security - Enayatollah Yazdani; Ji Zeng; Mohsen Bagheri (Asian Review of Political Economy, 2025)
Abstract  The failure of traditional approaches to provide security has resulted in introducing a new approach to security in the post-Cold War era known as "sustainable security." This issue is particularly important in the Middle East, where the security situation has deteriorated in recent decades due to traditional security approaches. The main question of this paper is, "What can be done to ensure long-term security in the Middle East?" This paper is based on the hypothesis that sustainable security can be achieved by addressing national security, regional security, global security, and human security at the same time. The paper addresses the problem of security in the Middle East using a descriptive-analytical methodology and utilizing a theoretical framework of critical approach to security. To do this, first, the relevant theoretical literature is discussed; second, the Middle East security issue is addressed. The factors most likely to contribute to long-term security at the human, national, regional, and global levels are discussed.